Presidential Prescriptions for State Policy: Obama's Race to the Top Initiative. (22nd May 2017) - Howell, William G.; Magazinnik, Asya
Abstract: With increasing frequency, U.S. presidents have orchestrated relations between federal and state governments. A defining feature of this "executive federalism" is a pragmatic willingness to both borrow from and reconstitute very different types of past federalisms. A case in point is President Barack Obama's Race to the Top (RttT) initiative, which sought to stimulate the adoption of specific education reforms in state governments around the country through a series of highly prescriptive but entirely voluntary policy competitions. This paper evaluates the results of such efforts. To do so, it draws on four original data sets: a nationally representative survey of state legislators, an analysis of State of the State speeches, another of state applications to the competitions themselves, and finally, an inventory of state policymaking trends in a range of education policies that were awarded under the competition. This paper then relies upon a variety of identification strategies to gauge the influence of RttT on the nation's education policy landscape. Taken as a whole the evidence suggests that RttT, through both direct and indirect means, augmented the production of state policies that were central components of the president's education agenda .